Comparing Students’ Engagement in Classroom Education Between China and Germany - Deng, Shu (Frontiers in Psychology, 2021)
Since the mid-1980s, there has been an academic shift toward students’ involvement in the learning process. A great number of studies have focused on the relationship between student engagement and educational achievement. They have highlighted that appropriate educational input and a supportive classroom environment are necessary, but optimum learning should occur when students are engaged with the curriculum as well as the institution, particularly in higher education institutions. Many scholars claimed that higher levels of engagement will help students deal with academic anxiety and develop a sense of belonging, which may lead to higher academic success. Educational experts and policymakers have begun to propose nationwide as well as international strategies and programs to promote student engagement in the classroom, which has led to the proposal of well-known programs such as the National Survey of Student Engagement, the UK Engagement Survey, and Program for International Student Assessment. Such engagement-centered international measures have been used across the globe (e.g., Germany) and also translated into different languages (e.g., Chinese). Although the findings of relevant studies confirm the effectiveness of engagement on learning achievement, there is still the need to conduct further (cross-sectional) studies considering the implementation of such programs in a different context. The present study is an attempt to review the related literature regarding student engagement among Chinese and German students across a variety of disciplines. The findings suggest that researchers should devote more time and budget to investigate the significance of learner engagement, especially in Germany as well as China.